The knowledge on contraindications for physical movement stimulation during pregnancy among prenatal course participants - Potoczek, Magdalena (Polish Journal of Public Health, 2010)
Introduction. Physical activity is nowadays a very important part of the pregnant women’s healthy lifestyle. Together with regular obstetric check-ups and a proper diet it is a significant part of the preparation for an active birth and maternity period. However, there is a group of medical contraindications that exclude physical movement stimulation during pregnancy. This group comprises mainly pathological conditions in pregnancy and mother diseases that can be hazardous to both woman and fetus’s health.Aim. The aim of this report is to define the pregnant women’s knowledge on contraindications for physical activity in the prenatal period.Results. The research based on a survey was conducted in 2008 and 2009 in the Dr Jadwiga Beaupre School of Childbearing in Kraków on the group of 100 women. The findings show that the respondents were aware of only the most obvious contraindications for physical activity in the prenatal period. Thus, there is an urgent need to increase women’s knowledge in this respect.